The Role of Motivating Teachers in Improving the Quality of Social Studies Learning in State Middle Schools in Maros Regency (Case Study at SMPN 23 Simbang and SMPN 22 Bantimurung) - Hasriani, Hasriani; W, Muhammad Fahreza; Hartini, Hartini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to find out and describe the role of driving teachers, the values of driving teachers, and the role and values of driving teachers as well as the challenges in implementing the role and values of driving teachers in improving the quality of education at SMPN 23 Simbang and SMPN 22 Bantimuring, Maros Regency. The method used in this research is a descriptive method with a qualitative approach. The data collection procedures in this research were interviews, observation, documentation and using source triangulation. There are five motivating teacher roles implemented at SMPN 23 Simbang and SMPN 22 Bantimurung. The role in question is being a learning leader, being a coach for other teachers, encouraging collaboration, realizing student leadership (student agency), mobilizing a community of practitioners... There are also five driving teacher values implemented at SMPN 23 Simbang and SMPN 22 Bantimurung, Maros Regency. These values are Student-Supporting, Independent, Reflective, Collaborative, and Innovative. There are several challenges faced in implementing the role and value of driving teachers, including: Limited resources, lack of understanding from other people, cultural changes and resistance to change, as well as student diversity and individual needs, and limited time and busy schedules. From the challenges faced, several alternative solutions that can be implemented are by holding training and professional development, as well as allocating adequate resources, establishing open and collaborative communication between all stakeholders, and optimizing existing (physical and non-physical) assets. This is also very relevant to the 10 concepts of educational quality management initiated by Edward Sallis.